The role of splanchnic congestion and the intestinal microenvironment in the pathogenesis of advanced heart failure. Issue 1 (March 2019) - Polsinelli, Vincenzo B.; Marteau, Lara; Shah, Sanjiv J.
Abstract : Purpose of review: Right-sided heart failure, which is often present in the setting of advanced heart failure, is associated with cardiac cachexia, the cardiorenal syndrome, and adverse outcomes. Improved understanding of venous congestion of the splanchnic circulation, which may play a key role in the pathogenesis of right-sided heart failure, could lead to novel therapeutics to ameliorate heart failure. Here we provide an overview of right-sided heart failure, splanchnic hemodynamics, fluid homeostasis, and the intestinal microenvironment. We review recent literature to describe pathophysiologic mechanisms and possible therapeutics. Recent findings: Several possible mechanisms centered around upregulation of sodium–hydrogen exchanger-3 (NHE3) may form a causal link between right ventricular dysfunction, splanchnic congestion, and worsening heart failure. These include an anaerobic environment in enterocytes, resulting in reduced intracellular pH; increased sodium absorption by the gut via NHE3; decreased pH at the intestinal brush border thus altering the gut microbiome profile; increased bacterial synthesis of trimethylamine N-oxide; and decreased bacterial synthesis of short-chain fatty acids causing abnormal intestinal barrier function. Summary: Splanchnic congestion in the setting of right-sided heart failure may serve an important role in the pathogenesis of advanced heart failure, and further exploration of these mechanisms may lead to new therapeutic advances.